Fully converged integral cross sections of collision induced dissociation, four-center, and single exchange reactions, and accuracy of the centrifugal sudden approximation in H2 + D2 reaction - Song, Hongwei (2013)
The initial state selected time-dependent wave packet method was employed to calculate the integral cross sections for the H2 + D2 reaction with and without the centrifugal sudden (CS) approximation by including all important K (the projection of the total angular momentum on the body-fixed axis) blocks. With a full-dimensional model, the first fully converged coupled-channel (CC) cross sections for different competitive processes from the ground rotational state were obtained: collision induced dissociation (CID), four-center (4C) reaction and single exchange (SE) reaction. The effect of the total angular momentum J on the reaction dynamics of H2 + D2 and the accuracy of the CS approximation have also been studied. It was found that the CID and SE processes occur in a wide range of J values while the 4C process can only take place in a narrow window of J values. For this reason, the CC cross section for the 4C channel is merely comparable to the SE channel. A comparison of the integral cross sections from CC and CS calculations showed that the CS approximation works well for the CID process but not for the 4C and SE processes, and the discrepancy between the CC and CS cross sections grows larger as the translational energy and/or the vibrational energy increase(s).